Effect of Interventions on Learning Burnout: A Systematic Review and Meta-Analysis - Tang, Lei; Zhang, Fan; Yin, Ruoyun; Fan, Zhaoya (Frontiers in Psychology, 2021)
Objectives: This study aimed to provide a comprehensive understanding of all intervention for learning burnout by meta-analyzing their effects. Methods: Relevant studies that had been published up to September 18, 2020, were identified through a systematic search of the PubMed, Web of Science, the China National Knowledge Infrastructure (CNKI), and Wan Fang databases. Eligible studies included randomized control trials of any learning burnout intervention conducted among students. The Jadad scale was used to evaluate the quality of the study. Random-effect meta-analyses, subgroup analyses, meta-regression analysis, and sensitivity analysis were conducted. Funnel plots and Egger's tests were used to evaluate publication bias. Duval and Tweedie’s nonparametric trim-and-fill method was used to adjust the effect of publication bias. Results: Of the 5245 articles found, 39 met the inclusion criteria for the systematic review. There were 3400 students, including 1847 students in the intervention group and 1553 in the control group. A meta-analysis of 44 studies showed that the interventions were effective. Subgroup analyses were conducted according to education, scales, intervention measures, and intervention time. The results showed that, compared with the control group, the learning burnout scores of undergraduates, secondary vocational students, and middle school students were significantly lower. Based on different scales, all interventions were also effective. The funnel plot was asymmetric and consistent with the results of Egger’s test. The trim-and-fill method was used, and seven missing studies were merged to obtain a symmetric funnel plot. Conclusions: This meta-analysis indicated that learning burnout interventions are effective. The subgroup analyses showed that group counseling is the most widely used, exercise intervention is probably the most effective, and eight weeks or more is the appropriate intervention time. An integrated intervention study based on the factors of learning burnout adds value. More studies are needed to supplement the results in the future.